Kontribusi Morfosintaksis Pada Tema Tentang Nasihat Dalam Kitab Al-Qirā’atu Al-Rasyīdah Terhadap Pembelajaran Bahasa Arab - Firman Firman; Darmawati Darmawati; Abd Halim K; Hamsa Hamsa (Journal on Education, 2024)
This study discusses the Contribution of Morphosyntax in the Book of al-Qirā'atu al-Rasyīdah to Arabic Language Learning. The main problem is how morphosyntax analysis can contribute to Arabic language learning. This type of research is library research using a descriptive design. The primary data used are the reading themes جزاء الصدق، الأدبُ أساس النجاح and الأمانة كنز in the book of al-Qirā'atu al-Rasyīdah through four stages of data collection, namely collecting materials, reading library materials, making notes and processing notes. The results of this study indicate that Morphosyntax in the book al-Qirā'atu al-Rasyīdah has contributed to the translation of an Arabic text, vocabulary related to morphosyntax, student skills (reading, writing and speaking) and increasing insight into the equivalent of morphosyntax terms. In addition, there is also a contribution in the form of vocabulary in the form of equivalent linguistic terms in morphology, syntax and Arabic language learning.